Extending Green Technology Adoption Models: Determinants of MSMEs’ Purchase Intention for a Hybrid Solar-Electric Cart in Urban Indonesia - Purwanto, Edi; Nugraha, Hari; Siregar, Ismail Alif (International Journal of Energy Economics and Policy, 2025)
The rapid urbanization of Indonesia’s metropolitan regions, particularly Jakarta and its surrounding cities (Jabodetabek), has intensified environmental challenges, including greenhouse gas emissions, air pollution, and energy dependency. The Hybrid Solar-Electric Cart (HSEC) has been developed to address these issues as an innovative, solar-assisted electric mobility solution tailored for micro, small, and medium enterprises (MSMEs). This study investigates the determinants influencing MSME owners’ intention to purchase the HSEC, focusing on environmental concern, performance expectancy, effort expectancy, charging time, price, and operational cost, with attitude as a mediating variable. A quantitative survey was conducted with 200 MSME owners in Jabodetabek, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results show that environmental concern, performance expectancy, price, and operational cost significantly enhance attitudes toward the HSEC, while charging time and effort expectancy exert no significant effect. Furthermore, attitude strongly mediates the relationship between these determinants and purchase intention. This study contributes theoretically by extending green technology adoption models to the context of small-scale, solar-assisted electric mobility in developing economies. This domain has received limited empirical attention. Practically, the findings provide actionable insights for policymakers (e.g., targeted subsidies and charging infrastructure), manufacturers (e.g., cost-effective production and after-sales support), and MSMEs (e.g., operational efficiency and long-term savings). By bridging the gap between technology readiness and market adoption, the study advances Indonesia’s transition toward a low-carbon economy while fostering sustainable growth among urban MSMEs.